Compressive strength of high strength concrete using British standard, euro code and non-destructive test approaches - Lee, Jin An (2010)
High strength concrete has been widely used in civil engineering in recent years. High strength concrete provides high compressive strength but lower the ductility than normal strength concrete. In this study, the compressive strength of cube and cylinder specimens was compared. Cube test is the common measurement of concrete compressive strength. According to British Standard 8110, the design of concrete structures is depend on the cube strength. In industries, the cube strength test is conducted to obtain the grade of concrete before it is applied to the work. In future, Eurocode 2 (EC2) will replace the existing British code 13S8 110 for the design of concrete structure. EC2 have some benefits compared to British Standard. Concrete strengths are referred to by cylinder strength, which are typically 10-20% less than the corresponding cube strengths. In this investigation, the concrete cube and cylinder were tested on 7 and 28 days of water curing. The result show that the value of cylinder strength is about 18-21% less than the cube strength. Nondestructive test which are Rebound Hammer test and Ultrasonic Pulse Velocity test was also used to test the concrete strength.